Adaptive Query Interface for Database Search (International Journal of Engineering and Computer Science, 2017)
Modern knowledge bases contain huge data with complex relations between the attributes. From these sort of databases obtaining satisfactory results is troublesome task. Use of traditional predefined query interfaces during this sort of databases doesn't provide satisfactory results. projected system generates query interface forms with user participation. User will provide feedback by click through therefore capturing user’s preference. Query form is adaptive since it dynamically refined until user gets satisfactory results.